Slurry for electrode formation
Patent Information
- Application Number
- JP2023130887
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2025-02-21
AI Technical Summary
【0016】 本発明のカーボンナノチューブスラリーは、カーボンナノチューブを比較的高濃度で均一に分散する反面、比較的低粘度のスラリーである。そのため、プレミキシング操作、分散機への送液操作及び分散機における分散操作を、大きな負荷をかけることなく行うことができる。以上により、本発明のカーボンナノチューブスラリーは、調製及び取り扱いが容易である。
Smart Images

Figure 2025025776000001 
Figure 2025025776000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a carbon nanotube slurry and an electrode-forming slurry used for producing electrodes of secondary batteries such as lithium ion secondary batteries. [Background technology]
[0002] With the spread of electric vehicles and the miniaturization, weight reduction, and improved performance of portable devices such as mobile phones and notebook personal computers, there is a demand for secondary batteries with high energy density, as well as for the secondary batteries with higher output and longer life. Under these circumstances, non-aqueous secondary batteries, including lithium-ion batteries using non-aqueous electrolytes, have come to be used in many devices due to their characteristics of high energy density and high voltage, and their development is being actively carried out.
[0003] Patent Document 1 discloses a slurry for forming an electrode of a lithium ion battery, which contains an electrode active material, a conductive assistant, a binder, and a polar solvent, and is characterized in that the conductive assistant has an average particle size of 500 nm or less when dispersed.
[0004] Patent Document 2 describes a carbon nanotube dispersion liquid containing carbon nanotubes (A), a solvent (B), and a dispersant (C) as a slurry for forming an electrode of a lithium ion battery, in which the carbon nanotubes (A) have a peak at a diffraction angle 2θ=25°±2° in a powder X-ray diffraction analysis, the half-width of the peak being 2° to 6°, and a peak width of 1560 to 1600 cm in a Raman spectrum. -1 The maximum peak intensity in the range of 1310 to 1350 cm is G. -1 The carbon nanotube dispersion liquid is characterized in that, when the maximum peak intensity within this range is defined as D, the G / D ratio is 0.5 to 5.0, and the dispersant (C) is a vinyl alcohol skeleton-containing resin. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2006-309958 A (Claims, Examples, etc.) [Patent Document 2] JP 2020-11873 A (Claims, Examples, etc.) Summary of the Invention [Problem to be solved by the invention]
[0006] In order to obtain high electrical properties in lithium ion secondary batteries, the conductivity of the electrodes is important. That is, the material constituting the electrodes is required to have high conductivity. In particular, carbon nanotubes with high conductivity are selectively used for the electrode forming slurry used to fabricate the electrodes.
[0007] Carbon nanotubes having a long fiber length are suitable for high electrical conductivity, but long carbon nanotubes usually have low dispersibility, and a slurry containing them has an extremely high viscosity. An object of the present invention is to provide a carbon nanotube slurry having excellent dispersibility and low viscosity.
[0008] On the other hand, when forming an electrode for a lithium ion secondary battery or the like using a slurry containing carbon nanotubes, the carbon nanotube slurry is generally applied to a current collector such as aluminum foil, and then dried to remove the solvent. However, the properties of the carbon nanotubes are not necessarily fully utilized in the electrode produced in this manner, and it has not been easy to industrially produce an electrode with low electrical resistivity. Another object of the present invention is to provide an electrode having high electrical conductivity and an electrode-forming slurry used for producing the electrode. [Means for solving the problem]
[0009] As a result of intensive research into the above-mentioned conventional problems, the inventors discovered that by using carbon nanotubes having specific properties, a suitable carbon nanotube slurry and electrode-forming slurry can be obtained, and based on this finding, they have completed the present invention.
[0010] That is, the present invention provides a method for producing a dispersion medium comprising at least carbon nanotubes, a dispersant, and a solvent, The carbon nanotube is 30 m 2 / g~70m 2 The carbon nanotube slurry has a BET specific surface area of 1.9 to 2.3 inclusive, and a peak intensity ratio G / D in Raman spectroscopy is 1.9 to 2.3 inclusive.
[0011] However, the peak intensity ratio G / D is 1570 to 1620 cm in the Raman spectrum. -1 The maximum intensity of the G-band scattered light peak in the range of 1320 to 1370 cm is defined as G. -1 This represents the ratio of the maximum intensity of the D band scattered light peak in the range of D.
[0012] Particularly preferably, the carbon nanotube slurry further has properties in which the carbon nanotubes have a fiber length of 500 μm to 3500 μm, a fiber width of 20 nm to 60 nm, and a 2θ peak half width of 0.7° to 1.2° in powder X-ray diffraction analysis.
[0013] The present invention also provides a liquid crystal display device comprising at least carbon nanotubes, a dispersant, an active material, and a solvent, The carbon nanotube is 30 m 2 / g~70m 2 The present invention relates to an electrode-forming slurry having a BET specific surface area of 1.9 to 2.3 inclusive, and a peak intensity ratio G / D in Raman spectroscopy.
[0014] Particularly preferably, in the electrode-forming slurry, the carbon nanotubes further have a fiber length of 500 μm to 3500 μm, a fiber width of 20 nm to 60 nm, and a 2θ peak half width of 0.7° to 1.2° in powder X-ray diffraction analysis.
[0015] Another aspect of the present invention is an electrode film containing at least 0.05 to 3.0 mass %, preferably 0.1 to 1.0 mass %, of carbon nanotubes, 0.0125 to 6.0 mass %, preferably 0.025 to 2.0 mass %, of a dispersant, and 80 to 98 mass %, preferably 90 to 97 mass %, of an active material, based on the total mass of the electrode film, The carbon nanotube is 30 m 2 / g~70m 2 / g and a peak intensity ratio G / D in Raman spectroscopy of 1.9 to 2.3, wherein the peak intensity ratio G / D is as defined above. Effect of the Invention
[0016] The carbon nanotube slurry of the present invention is a slurry in which carbon nanotubes are uniformly dispersed at a relatively high concentration, but has a relatively low viscosity. Therefore, the premixing operation, the liquid feeding operation to the disperser, and the dispersing operation in the disperser can be performed without applying a large load. As a result, the carbon nanotube slurry of the present invention is easy to prepare and handle.
[0017] The electrode-forming slurry of the present invention has excellent dispersibility and low viscosity, and therefore can be easily prepared industrially and has good applicability to a current collector. Furthermore, by using the electrode-forming slurry of the present invention, an electrode film having high conductivity, i.e., low electrical resistivity, can be produced. The electrode film having the composition of the present invention has low electrical resistivity and exhibits excellent performance as an electrode for a lithium ion secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Carbon nanotubes The carbon nanotubes used in the present invention are cylindrical substances made of carbon and having a diameter on the order of nanometers. They include single-walled carbon nanotubes as well as multi-walled carbon nanotubes in which two or more carbon nanotubes with different diameters are layered together.
[0019] The BET specific surface area of the carbon nanotubes used in the present invention is 30 m 2 / g or more 70m 2 / g, preferably less than 35m 2 / g over 65m 2 The BET specific surface area of the carbon nanotubes can be measured using a specific surface area measuring device.
[0020] One of the features of the present invention is the use of carbon nanotubes with a relatively small BET specific surface area. Carbon nanotube slurries and electrode-forming slurries using carbon nanotubes with a BET specific surface area within the above range have excellent dispersibility and low slurry viscosity even when the fiber length of the carbon nanotubes is long. In addition, the electrical resistance of the electrode film produced from such electrode slurries can be reduced.
[0021] On the other hand, when the carbon nanotube slurry and the electrode-forming slurry contain carbon nanotubes having a BET specific surface area exceeding the above range, the slurry dispersibility is reduced and the slurry viscosity is increased, making it difficult to handle. As a result, the electrode-forming slurry in such a case is disadvantageous in industrially producing electrodes.
[0022] The mechanism by which the carbon nanotubes used in the present invention exert the effects of the present invention is presumed to be as follows. That is, carbon nanotubes are generally in a powder state, in the form of bundles of carbon nanotubes. If there are gaps in the bundles, or if they are in a non-uniform and sparse state, the BET specific surface area is large. On the other hand, carbon nanotubes with a relatively small BET specific surface area used in the present invention have very few gaps in the bundles and have a uniform and dense structure, which suppresses swelling due to the intrusion of a solvent. Therefore, the amount of solvent held by the carbon nanotubes in the slurry is reduced, which suppresses swelling of the carbon nanotubes and suppresses an increase in the viscosity of the slurry.
[0023] The carbon nanotubes used in the present invention are carbon nanotubes having a peak intensity ratio G / D in the Raman spectrum of 1.9 to 2.3. Here, the peak intensity ratio G / D is the peak intensity ratio between 1570 and 1620 cm -1 The maximum intensity of the G-band scattered light peak in the range of 1320 to 1370 cm is defined as G. -1 The maximum intensity of the D-band scattered light peak within the range is defined as D, and the ratio is expressed as D. Raman spectra can be measured by detecting Raman scattered light using a Raman spectrometer.
[0024] The peak intensity ratio G / D in Raman spectroscopy reflects the crystallinity of the carbonaceous material. If the crystallinity of the carbonaceous material is too high, the carbon edges decrease due to the development of the graphite structure, and the coordination sites of the electrolyte decrease, resulting in problems such as a decrease in characteristics at low temperatures and an increase in electrical resistivity. If the crystallinity of the carbonaceous material is too low, the amount of amorphous material increases, the electrical resistivity increases, and the utilization efficiency of the electric double layer at the interface between the electrolyte and the electrode material decreases. If carbon nanotubes with a G / D value within the above range are used, there is an advantage that an electrode having few defects, high resistance to high voltage driving, and high conductivity over a long period of time can be obtained when the electrode is manufactured.
[0025] The carbon nanotubes used in the present invention are fibers having a fiber length of preferably 500 μm to 3500 μm, more preferably 800 μm to 3300 μm, and even more preferably 700 μm to 3000 μm, and a fiber width of preferably 20 nm to 100 nm, and more preferably 25 nm to 60 nm. The fiber length and fiber width of the carbon nanotubes refer to the arithmetic average values of the fiber lengths and fiber widths of a sufficient number n, measured using an image obtained by an electron microscope.
[0026] The use of carbon nanotubes having a fiber length within the above range is preferable because it allows the preparation of an electrode having high conductivity, i.e., an electrode having low electrical resistivity. On the other hand, the use of carbon nanotubes having a fiber length shorter than the above range makes the conductive path more likely to be broken when the electrode is prepared, resulting in a high apparent electrical resistivity. Furthermore, it is preferable to use carbon nanotubes having a fiber width within the above range, since high dispersibility can be obtained in the carbon nanotube slurry and the electrode-forming slurry.
[0027] Furthermore, the carbon nanotubes used in the present invention preferably have a peak at a diffraction angle 2θ=25°±2° in powder X-ray diffraction, and the peak half-width is 0.7° to 1.2°. The powder X-ray diffraction can be performed using an X-ray diffractometer. The half-width of the 2θ peak detected by powder X-ray diffraction analysis is an index of the layer structure of the carbon nanotube. It is considered that the smaller the half-width of the peak, the more layers of the multi-walled carbon nanotube there are, and conversely, the larger the half-width of the peak, the fewer layers of the carbon nanotube there are. The use of carbon nanotubes with a half-width of the peak within the above range has the advantage of achieving both electrical conductivity and dispersibility.
[0028] The carbon nanotubes used in the present invention are produced, for example, by a fluidization method in which a raw material gas is introduced into a high-temperature chamber containing a powdered catalyst and grown on the catalyst surface in a fluidized state. Alternatively, the carbon nanotubes are produced by a substrate method in which a raw material gas is introduced into a high-temperature chamber containing a substrate with a catalyst attached thereon and grown chemically on the substrate. Carbon nanotubes produced by the above-mentioned method or other methods can be used as long as they have the properties specified in the present invention.
[0029] Carbon nanotubes may contain heavy metals of group VIII, group VIIA, and group VIA, such as Fe, Co, and Ni, derived from the manufacturing process. The demetallization operation is an operation for removing the amount of heavy metals contained in the carbon nanotubes and adjusting the content thereof. Applicable demetallization operations include acid treatment, base treatment, and baking treatment in an inert atmosphere, and can be carried out alone or in combination of two or more of these. The amount of heavy metals contained in the carbon nanotubes can be measured by extracting the carbon nanotubes with an acidic aqueous solution after baking and using an ICP emission spectrometer.
[0030] The total content of heavy metals contained in the carbon nanotubes after the demetallization operation is preferably less than 5000 ppm, more preferably less than 3000 ppm, and even more preferably less than 1000 ppm. If the total content of heavy metals in the carbon nanotubes is 5,000 ppm or more, this is undesirable because the heavy metals will dissolve from the electrodes into the electrolyte in the produced secondary battery, reducing the charge / discharge cycle characteristics and making it impossible to extend the battery's life.
[0031] The carbon nanotubes used in the carbon nanotube slurry and electrode-forming slurry of the present invention are preferably those that have been subjected to one or a combination of the following treatments: pulverization, classification, and demetallization. These treatments allow the adjustment of various properties of the carbon nanotubes.
[0032] The pulverization operation is an operation for pulverizing carbon nanotubes to an appropriate size. Applicable pulverization operations include dry pulverization using a pin mill, pulverizer, hammer mill, jet mill, ball mill, Henschel mixer, or attritor, and wet pulverization using an ultrasonic disperser, disperser, homomixer, rotation-revolution mixer, planetary mixer, high-pressure homogenizer, paint conditioner, colloid mills, bead mill, cone mill, wet jet mill, or thin film swirling high-speed mixer.
[0033] The classification operation is an operation for adjusting the size of carbon nanotubes. Applicable classification operations can be performed by a device using gravity, inertia, or centrifugal force, or a device using a filter, in a dry method or a wet method.
[0034] The carbon nanotube slurry of the present invention can contain carbon nanotubes at a relatively high concentration. Specifically, the carbon nanotube content can be preferably 0.1% by mass to 3.0% by mass, more preferably 0.15% by mass to 1.0% by mass, and even more preferably 0.2% by mass to 0.5% by mass, based on the total amount of the carbon nanotube slurry and the electrode forming slurry. When the carbon nanotube content of the electrode forming slurry is within this range, the slurry can be uniformly applied to the current collector, and the performance of the secondary battery electrode produced from the slurry can be ensured.
[0035] The carbon nanotube slurry of the present invention is a slurry in which the carbon nanotubes are uniformly dispersed and has a low viscosity. The viscosity of the carbon nanotube slurry of the present invention is 38.3 s -1 In this case, the viscosity is preferably 5 to 100,000 mPa·s, more preferably 10 to 10,000 mPa·s, even more preferably 20 to 1,000 mPa·s, and still more preferably 30 to 700 mPa·s.
[0036] <Dispersant> The dispersant is a solvent soluble polymer that disperses the carbon nanotubes well in the solvent, resulting in a stable slurry. When the solvent for the carbon nanotube slurry and electrode-forming slurry of the present invention is an aqueous solvent, preferred dispersants include polyvinylpyrrolidone, carboxymethylcellulose or its salts (alkali metal salts such as Li, Na, and K), cellulose nanofibers, modified polyvinyl butyral, and acrylate polymers.
[0037] When the solvent of the carbon nanotube slurry and the electrode forming slurry of the present invention is a non-aqueous solvent, preferred dispersants include polyvinylpyrrolidone, polyvinyl butyral, acrylate polymers, styrene acrylate copolymers, and polyvinylidene fluoride.
[0038] The content of the dispersant in the carbon nanotube slurry and electrode-forming slurry of the present invention is preferably 3 to 300 parts by mass, more preferably 5 to 200 parts by mass, further preferably 8 to 150 parts by mass, and particularly preferably 10 to 100 parts by mass, relative to 100 parts by mass of the carbon nanotubes. When the amount of the dispersant is within this range, the dispersibility of the electrode slurry is exhibited, and the performance of the secondary battery electrode produced from the electrode slurry is not adversely affected.
[0039] <solvent> The solvents used in the carbon nanotube slurry and electrode-forming slurry of the present invention include aqueous and non-aqueous solvents. The amount of the solvent mixed in the electrode-forming slurry is preferably 20 to 70% by mass, more preferably 30 to 60% by mass, based on the total amount of the electrode-forming slurry, whether the solvent is aqueous or non-aqueous.
[0040] The solvent in one embodiment of the carbon nanotube slurry and the electrode-forming slurry of the present invention is an aqueous solvent containing water. As the aqueous solvent, water (e.g., ion-exchanged water, distilled water, tap water, etc.) or a mixed solvent of water and a water-soluble solvent can be used.
[0041] Examples of water-soluble solvents that can be used in the mixed solvent include alkylene glycols such as ethylene glycol, triethylene glycol, tetraethylene glycol, propylene glycol, dipropylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 2,3-butanediol, 1,3-butanediol, 1,4-butanediol, 1,2-pentanediol, 1,5-pentanediol, 2,5-hexanediol, 3-methyl-1,3-butanediol, 2-methylpentane-2,4-diol, 3-methylpentane-1,3,5-triol, and 1,2,3-hexanetriol; polyalkylene glycols such as polyethylene glycol and polypropylene glycol; glycerols such as glycerol, diglycerol, and triglycerol;
[0042] Examples of the alkyl ether include lower alkyl ethers of glycols such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monomethyl ether, and diethylene glycol mono-n-butyl ether; amides such as N-methyl-2-pyrrolidone, 1,3-dimethyl-2-imidalidinone, N,N-dimethylacetamide, and N,N-dimethylformamide; and ketones such as acetone.
[0043] The content of the water-soluble solvent in the mixed solvent is preferably 0.1 to 30% by mass, more preferably 1 to 20% by mass, based on the total amount of the mixed solvent. Within this range, good fluidity of the electrode-forming slurry can be obtained.
[0044] In another embodiment of the carbon nanotube slurry and the electrode forming slurry of the present invention, the solvent is a non-aqueous solvent that does not substantially contain water. The water content allowed in the non-aqueous solvent is preferably less than 5000 mg / L, more preferably less than 3000 mg / L, and even more preferably 1000 mg / L or less. When the water content is within this range, the fluidity of the electrode forming slurry is ensured. The amount of water contained in the non-aqueous solvent can be measured by a Karl Fischer moisture meter (coulometric titration method).
[0045] Examples of solvents that can be used as non-aqueous solvents include methanol, ethanol, isopropanol, butanol, ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, dipropylene glycol dimethyl ether, dipropylene glycol methyl-n-propyl ether, diethylene glycol diethyl ether, propylene glycol monomethyl ether, methyl monoglycidyl ether, ethyl monoglycidyl ether, butyl monoglycidyl ether, phenyl monoglycidyl ether, methyl diglycidyl ether, ethyl diglycidyl ether, butyl diglycidyl ether, phenyl diglycidyl ether, methylphenol monoglycidyl ether, ethylphenol monoglycidyl ether, butylphenol monoglycidyl ether, butylphenyl ether, dioxane, dioxolane, anisole, ethyl benzyl ether, cresyl methyl ether, diphenyl ether, dibenzyl ether, phenetole,
[0046] Ethylene glycol monoacetate, ethylene glycol monomethyl ether acetate, propylene glycol diacetate, dipropylene glycol methyl ether acetate, 1,4-butanediol diacetate, 1,3-butylene glycol diacetate, 1,6-hexanediol diacetate, propylene glycol diacetate, ethylene glycol monoethyl ether acetate, diethylene glycol monoacetate, propylene glycol monoacetate, dipropylene glycol monoacetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate,
[0047] Methyl acetate, ethyl acetate, propyl acetate, butyl acetate, cyclohexyl acetate, methyl pyruvate, ethyl pyruvate, methyl methoxypropionate, ethyl ethoxypropionate, methyl butyrate, ethyl butyrate, propyl butyrate, butyl butyrate, methyl lactate, ethyl lactate, γ-butyrolactone, N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, 4-vinylpyridine,
[0048] Methyl methacrylate, 2-hydroxyethyl acrylate, tetrahydrofurfuryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl methacrylate, hydroxypropyl methacrylate, glycidyl methacrylate, neopentyl glycol diacrylate, hexanediol diacrylate, trimethylolpropane triacrylate, acetone, methyl ethyl ketone, methyl-n-pentyl ketone, methyl isobutyl ketone, methyl isopentyl ketone, 2-heptanone, cycloheptanone, cyclohexanone,
[0049] Examples of the non-aqueous solvent include hexane, cyclohexane, methylcyclohexane, ethylcyclohexane, heptane, octane, benzene, toluene, xylene, cymene, mesitylene, styrene, ethylbenzene, diethylbenzene, isopropylbenzene, pentylbenzene, mineral spirits, perfluorocarbons, hydrofluoroethers, hydrochlorofluorocarbons, hydrofluorocarbons, perfluoropolyethers, various silicone oils, various naphthenic solvents, various paraffinic solvents, and various isoparaffinic solvents. One solvent selected from the above group of non-aqueous solvents, or a mixed solvent consisting of two or more solvents, can be used.
[0050] Among these non-aqueous solvents, dioxolane, butyl butyrate, N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, methyl ethyl ketone, cyclohexanone, and isoparaffin-based solvents are preferred.
[0051] (Production of Carbon Nanotube Slurry) The carbon nanotube slurry of the present invention can be produced through a dispersion step in which at least the carbon nanotubes, dispersant, and solvent are charged into a mixer and stirred and mixed. The dispersion step in the production of carbon nanotube slurry can be carried out by dispersing using, for example, an ultrasonic disperser, a disperser, a homomixer, a rotation-revolution mixer, a Henschel mixer, a planetary mixer, or other mixer; a (high-pressure) homogenizer, a paint conditioner, colloid mills, a media-type disperser such as a bead mill, a cone mill, a ball mill, a sand mill, an attritor, a pearl mill, or a coball mill; a media-less disperser such as a wet jet mill or a thin film rotating high-speed mixer; or other dispersing devices such as a roll mill. From the viewpoints of the stability of the dispersing action and the dispersing efficiency, the preferred dispersing apparatus is a thin film rotary type high speed mixer or a bead mill.
[0052] The carbon nanotube slurry of the present invention has excellent fluidity. Specifically, the slurry has a shear rate of 38.3 s-1 The viscosity at 25°C can be preferably 5 to 100,000 mPa·s, more preferably 10 to 10,000 mPa·s, even more preferably 20 to 1,000 mPa·s, and still more preferably 30 to 700 mPa·s. The viscosity of the carbon nanotube slurry can be measured using an E-type rotational viscometer (TV-22, manufactured by Toki Sangyo Co., Ltd.).
[0053] <Slurry for forming electrodes> The carbon nanotube slurry of the present invention can be suitably used as an electrode slurry for producing a positive electrode or a negative electrode of a secondary battery such as a lithium ion battery. The electrode slurry of the present invention can be obtained by adding an active material such as a positive electrode active material or a negative electrode active material to the above carbon nanotube slurry, and can be used as a positive electrode slurry or a negative electrode slurry.
[0054] That is, one aspect of the present invention is an electrode slurry containing at least the carbon nanotubes, a dispersant, a solvent and an active material. Whether the electrode slurry is a positive electrode slurry containing a positive electrode active material or a negative electrode slurry containing a negative electrode active material, the types and compounding ratios of the carbon nanotubes, dispersant, and solvent used are the same as those described above for the carbon nanotube slurry.
[0055] <Active material> In the electrode slurry of the present invention, a positive electrode active material or a negative electrode active material is blended as an active material for an electrode. Hereinafter, the electrode slurry blended with the positive electrode active material may be referred to as a positive electrode slurry, and the electrode slurry blended with the negative electrode active material may be referred to as a negative electrode slurry.
[0056] <Active material for positive electrode> The positive electrode slurry contains a positive electrode active material. In the positive electrode slurry, the content of the positive electrode active material is preferably 50 to 70 mass % and more preferably 50 to 63 mass % based on the total amount of the positive electrode slurry. When the content of the positive electrode active material in the positive electrode slurry is within this range, the fluidity of the slurry can be maintained while ensuring the performance of the electrode to be produced.
[0057] Examples of the positive electrode active material include composite oxides of lithium and transition metals such as lithium-nickel composite oxide, lithium-cobalt composite oxide, lithium-manganese composite oxide, lithium-nickel-manganese composite oxide, lithium-nickel-cobalt composite oxide, lithium-nickel-aluminum composite oxide, lithium-nickel-cobalt-aluminum composite oxide, lithium-nickel-manganese-cobalt composite oxide, lithium-nickel-manganese-aluminum composite oxide, and lithium-nickel-cobalt-manganese-aluminum composite oxide; TiS 2 , FeS, MoS 2 Transition metal sulfides such as MnO, V 2 O 5 , V 6 O 13 , TiO 2 and olivine-type lithium phosphate.
[0058] The olivine-type lithium phosphate is a compound containing at least one element selected from the group consisting of Mn, Cr, Co, Cu, Ni, V, Mo, Ti, Zn, Al, Ga, Mg, B, Nb, and Fe, lithium, phosphorus, and oxygen. The olivine-type lithium phosphate may be a compound in which some of the elements are replaced with other elements in order to improve the properties.
[0059] The positive electrode active material is preferably a lithium-nickel composite oxide, more preferably a lithium-nickel composite oxide represented by the formula: LiNi X M1 Y M2 Z O 2(M1 and M2 are at least one metal element selected from the group consisting of Al, B, alkali metals, alkaline earth metals, and transition metals; 0.8≦X≦1.0, 0≦Y≦0.2, 0≦Z≦0.2), or lithium phosphate. These positive electrode active materials may be used alone or in combination of two or more.
[0060] The positive electrode slurry may further contain a solid electrolyte such as a sulfide solid electrolyte, an oxide solid electrolyte, a dry polymer electrolyte, a gel polymer electrolyte, or a quasi-solid electrolyte.
[0061] <Active material for negative electrode> The negative electrode slurry contains a negative electrode active material. In the negative electrode slurry, the content of the negative electrode active material is preferably 30 to 60 mass % and more preferably 35 to 55 mass % based on the total amount of the negative electrode slurry. When the content of the negative electrode active material in the negative electrode slurry is within this range, the fluidity of the slurry can be maintained while ensuring the performance of the electrode to be produced.
[0062] As the negative electrode active material, metal oxide particles, silicon particles, and spherical graphite can be used, with metal oxide particles being particularly suitable.
[0063] As the metal oxide particles, for example, titanium oxide can be used. As the titanium oxide, one capable of absorbing and releasing lithium can be used, and examples thereof include spinel-type lithium titanate, ramsdellite-type lithium titanate, titanium-containing metal composite oxide, and titanium dioxide (TiO) having a monoclinic crystal structure. 2 (B)) and anatase type titanium dioxide, etc. can be used.
[0064] Spinel-type lithium titanate includes Li 4+x Ti 5 O 12(x varies in the range of -1≦x≦3 depending on the charge / discharge reaction). Ramsdellite-type lithium titanate includes Li 2+y Ti 3 O 7 (y varies in the range of -1≦y≦3 depending on the charge / discharge reaction). TiO 2 (B) and anatase type titanium dioxide include Li 1+z TiO 2 (z changes in the range of -1≦z≦0 due to the charge and discharge reaction.)
[0065] Examples of titanium-containing metal composite oxides include metal composite oxides containing Ti and at least one element selected from the group consisting of P, V, Sn, Cu, Ni, and Fe. Examples of metal composite oxides containing Ti and at least one element selected from the group consisting of P, V, Sn, Cu, Ni, and Fe include TiO 2 -P 2 O 5 , TiO 2 -V 2 O 5 , TiO 2 -P 2 O 5 -SnO 2 , TiO 2 -P 2 O 5 -MeO (Me is at least one element selected from the group consisting of Cu, Ni, and Fe).
[0066] Such a metal composite oxide preferably has a microstructure with low crystallinity, in which a crystalline phase and an amorphous phase coexist, or in which an amorphous phase exists alone, which can further improve cycle performance.
[0067] The negative electrode slurry may further contain a solid electrolyte such as a sulfide solid electrolyte, an oxide solid electrolyte, a dry polymer electrolyte, a gel polymer electrolyte, or a quasi-solid electrolyte.
[0068] Conductive Materials The electrode forming slurry of the present invention may further contain a conductive material other than carbon nanotubes (hereinafter, simply referred to as a "conductive material"). By adding the conductive material, the conductivity of the secondary battery electrode produced from the slurry can be increased.
[0069] Conductive materials that can be used include conductive carbon particles and conductive carbon fibers made of graphitic carbonaceous materials. Examples of the conductive carbon particles that can be used include carbon black particles such as acetylene black, ketjen black, etc. Examples of the conductive carbon fibers include carbon nanofibers other than carbon nanotubes.
[0070] The conductive carbon particles have a specific gravity difference of ±0.2 g / cm from the carbon nanotubes. 3 A particle diameter within this range is preferable because separation due to differences in specific gravity is unlikely to occur when the electrode-forming slurry is stored. Furthermore, it is more preferable that the primary particle diameter of the conductive material particles is 1 to 70 nm, preferably 1 to 50 nm, and more preferably 1 to 40 nm, from the viewpoints of conductivity and stability. The primary particle diameter of the conductive carbon particles refers to the arithmetic mean value of the outer diameter of a sufficient number n measured using an image under an electron microscope.
[0071] The fiber width of the conductive carbon fiber is preferably 1 to 500 nm, more preferably 1 to 400 nm, and even more preferably 1 to 200 nm, from the viewpoints of conductivity and stability. Particularly preferably, it is 1 nm or more and 90 nm or less, 3 nm or more and 30 nm or less, and furthermore, 3 nm or more and 15 nm or less. The fiber width of the conductive carbon fiber refers to the arithmetic average value of a sufficient number of fiber widths measured using an image by an electron microscope.
[0072] The content of the conductive material to be mixed is preferably 0.5 to 10 mass %, more preferably 0.5 to 7 mass %, and particularly preferably 0.5 to 5 mass %, based on the total amount of the electrode-forming slurry.
[0073] <Binding material> The above-mentioned electrode-forming slurry preferably further contains a binding material (binder). Examples of binders that can be used include fluororesins such as polyimide resins, polyvinylidene fluoride (PVdF), polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymers, hexafluoropropylene-vinylidene fluoride copolymers, and tetrafluoroethylene-perfluorovinyl ether copolymers, polyolefin resins such as polyethylene and polypropylene, polyvinylpyrrolidone, polyvinyl alcohol, styrene-butadiene rubber (SBR), and acrylic resins. Two or more types of binders may be used in combination.
[0074] The amount of the binder used is preferably 0.05 to 5 parts by mass, more preferably 0.1 to 4.5 parts by mass, and even more preferably 0.5 to 4.5 parts by mass, relative to 100 parts by mass of the active material in each electrode slurry for secondary batteries. When the amount of the binder added is within this range, an electrode having high adhesion to the current collector is obtained without adversely affecting the battery capacity or charge / discharge characteristics.
[0075] In addition to the above components, the electrode slurry of the present invention may further contain a leveling agent, a solid electrolyte, a preservative, etc., as appropriate.
[0076] <Production of Electrode-Forming Slurry> The electrode-forming slurry of the present invention is produced by mixing and homogenizing at least the carbon nanotubes having the above-mentioned properties, the dispersant, the active material and the solvent. For example, the slurry for forming an electrode can be prepared by premixing carbon nanotubes, a dispersant, an active material, a solvent, etc., and then feeding the mixture into a mixer and stirring and mixing the mixture for dispersion. Alternatively, the slurry for forming an electrode can be prepared by premixing carbon nanotubes, a dispersant, a solvent, etc., and then feeding the mixture into a mixer and stirring and mixing the mixture for dispersion. The slurry can then be mixed with the active material and homogenized to prepare the slurry for forming an electrode.
[0077] The dispersion treatment in the production of the electrode-forming slurry can be carried out using, for example, an ultrasonic disperser, a mixer such as a disperser, a homomixer, a rotation-revolution mixer, a Henschel mixer, or a planetary mixer, a (high-pressure) homogenizer, a paint conditioner, colloid mills, a media-type disperser such as a bead mill, a cone mill, a ball mill, a sand mill, an attritor, a pearl mill, or a coball mill, a media-less disperser such as a wet jet mill or a thin film rotary high-speed mixer, or other dispersing apparatus such as a roll mill. From the viewpoints of the stability of the dispersing action and the dispersing efficiency, the preferred dispersing apparatus is a thin film rotary type high speed mixer or a bead mill.
[0078] The electrode forming slurry of the present invention has excellent fluidity. Specifically, the slurry has a shear rate of 38.3 s -1 The viscosity at 25° C. can be preferably 5 to 500,000 mPa·s, more preferably 10 to 10,000 mPa·s, even more preferably 20 to 1,000 mPa·s, and still more preferably 30 to 700 mPa·s.
[0079] <Preparation of electrode film> The electrode-forming slurry of the present invention can be applied onto a current collector and dried to prepare an electrode film for a positive electrode or a negative electrode. First, the electrode forming slurry is applied onto a current collector. The current collector is a substrate that holds an electrode film of a secondary battery such as a lithium ion secondary battery. The material and shape of the current collector used as the substrate of the electrode film are not particularly limited, and can be appropriately selected according to the secondary battery to be applied. Examples of the material of the current collector include glass, resin, metals and alloys such as aluminum, copper, nickel, titanium, and stainless steel. In addition, as the shape of the current collector, a flat metal foil is preferably used, and a foil with a roughened surface, a perforated foil, and a mesh-shaped foil can also be used.
[0080] Examples of methods for applying the electrode-forming slurry to the current collector include die coating, dip coating, roll coating, doctor coating, knife coating, spray coating, gravure coating, screen printing, and electrostatic painting. After application, the surface may be smoothed using a lithographic press or a calendar roll.
[0081] Next, the current collector coated with the electrode-forming slurry is dried, thereby producing an electrode in which a solid electrode film is formed on the current collector. The electrode-forming slurry after application can be dried using natural drying, a blower dryer, a hot air dryer, an infrared heater, a far-infrared heater, or the like. The thickness of the electrode film formed on the current collector after drying is generally from 1 μm to 500 μm, and preferably from 10 μm to 300 μm.
[0082] The electrode-forming slurry of the present invention is used to prepare an electrode film suitable as an electrode for a lithium-ion secondary battery, etc. The formed electrode film contains at least carbon nanotubes, a dispersant, and an active material, and specifically contains 0.05 to 3.0 mass %, preferably 0.1 to 1.0 mass %, carbon nanotubes, 0.0125 to 6.0 mass %, preferably 0.025 to 2.0 mass %, and active material, 80 to 98 mass %, preferably 90 to 97 mass %, based on the total amount of the electrode film.
[0083] The electrode film produced from the electrode-forming slurry of the present invention has low electrical resistivity. For example, the surface resistivity of this electrode film can be 5000Ω / □ or less, preferably 4000Ω / □ or less, and constitutes a lithium ion secondary battery with excellent battery capacity, cycle characteristics, and Coulombic efficiency (discharge amount / charge amount).
[0084] <Lithium-ion secondary battery> A lithium ion secondary battery is usually composed of a positive electrode, a negative electrode, an electrolyte, a non-aqueous solvent, and a separator that is provided as necessary, and can be formed into various shapes according to the purpose of use, such as a cylindrical shape, a prismatic shape, a gum shape, a coin shape, a button shape, a pin shape, a paper shape, etc. An electrode prepared by coating the above-mentioned electrode slurry can be used as the positive electrode or negative electrode of the lithium ion secondary battery. Hereinafter, a lithium ion secondary battery constructed using an electrode prepared from the positive electrode slurry or the negative electrode slurry of the present invention will be described.
[0085] For the positive electrode, an electrode prepared by coating the above-mentioned positive electrode slurry containing a positive electrode active material on a current collector and drying the coating can be used. For the negative electrode, an electrode prepared by coating the above-mentioned negative electrode slurry containing the negative electrode active material on a current collector and drying it can be used.
[0086] The electrolyte can be a Li salt with mobile ions, such as LiBF 4 , LiClO 4 , LiPF 6 , LiAsF 6 , LiSbF 6 , LiCF 3 SO 3 , Li(CF 3 SO 2 ) 2 N, LiC 4 F 9 SO 3 , Li(CF 3 SO 2 ) 3 C, LiI, LiBr, LiCl, LiAlCl 4 , LiHF 2 , LiSCN, and LiBPh 4 (wherein Ph represents a phenyl group).
[0087] Examples of non-aqueous solvents include aprotic polar solvents such as carbonates (e.g., ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate); lactones (e.g., γ-butyrolactone, γ-valerolactone, and γ-octanoic lactone); ethers (e.g., tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-methoxyethane, 1,2-ethoxyethane, and 1,2-dibutoxyethane); esters (e.g., methyl formate, methyl acetate, and methyl propionate); sulfoxides (e.g., dimethyl sulfoxide and sulfolane); and nitriles (e.g., acetonitrile). These solvents may be used alone or in combination of two or more.
[0088] Examples of the separator include polyethylene nonwoven fabric, polypropylene nonwoven fabric, polyamide nonwoven fabric, and these fabrics that have been subjected to a hydrophilic treatment. EXAMPLES
[0089] Examples of the embodiment of the present invention will be described below with reference to Examples. Note that the properties of each carbon nanotube (CNT) used in the preparation of the electrode-forming slurry in the following Examples and Comparative Examples were measured by the following methods.
[0090] [BET specific surface area] The BET specific surface area of the carbon nanotubes was measured using a specific surface area measuring device (Macsorb model HM-1208, manufactured by Mountec Co., Ltd.) under the conditions of a single-point BET method and pretreatment at 110° C. for 30 minutes.
[0091] [Raman spectrum] Measurements were performed using a Raman spectrometer (Thermo Fisher Scientific, DXR2xi Raman Imaging Microscope) at a laser wavelength of 532 nm. The measurement conditions were laser output 2.0 mW, exposure time 0.1 s, scan count 10 times, objective lens magnification 50x, aperture 50 μm confocal pinhole, grating full range, measurement wavelength 50 to 3400 cm -1 It was decided.
[0092] Measurements were performed at five random points for each sample, with no duplicates. Among the peaks obtained, the 1580 cm -1 The maximum peak intensity around G is 1350 cm -1 The maximum peak intensity in the vicinity was taken as D, and the G / D ratio for each measurement was calculated. The arithmetic mean of the G / D ratios of five points on the same sample was taken as the peak ratio (G / D) of the Raman spectrum of that sample.
[0093] [Fiber length / width] The carbon nanotubes were observed using a scanning electron microscope (Hitachi High-Tech Corporation, S-3400N; SEM), and the arithmetic mean value of the fiber lengths of 10 carbon nanotubes measured using an image at a magnification of 1000 times was determined as the fiber length of the carbon nanotube. The carbon nanotubes were also observed using a transmission electron microscope (Hitachi High-Tech Corporation, H-7650; TEM), and the arithmetic mean value of the fiber widths of 10 carbon nanotubes measured using an image at a magnification of 50,000 times was determined as the fiber width of the carbon nanotube.
[0094] [Peak half width] The carbon nanotubes were observed using a powder X-ray diffraction analyzer (Rigaku Corporation, miniflex600) under conditions of a tube voltage of 40 kV, a tube current of 15 mA, a scan speed of 2° / min, and a data sampling of 0.02°, and the average 2θ peak half-width of 10 carbon nanotubes was calculated.
[0095] Example 1 <Preparation of carbon nanotube slurry> A 300 mL beaker was charged with 1.0 part by mass of commercially available carbon nanotube A, 0.5 parts by mass of sodium carboxymethylcellulose (CMC, Daicel Miraizu Co., Ltd., 1190) as a dispersant, and 198.5 parts by mass of water as a solvent, and the mixture was stirred (premixed) for 1 hour using a disperser at a stirring speed (300 rpm) that did not introduce bubbles, to obtain a premixed liquid.
[0096] The above premixed liquid was put into a dispersing machine (DYNO-MILL, manufactured by Shinmaru Enterprises Co., Ltd.), and then 970 parts by mass of zirconia beads (bead diameter Φ0.5 mm) were added, and a dispersion process was performed at a peripheral speed of 14 m / s. The beads were then separated to obtain a carbon nanotube slurry in which the carbon nanotubes were uniformly dispersed. The dispersibility (dispersion conditions) of the obtained carbon nanotube slurry was visually evaluated as follows: A if the mixing time required for the mixture to become a uniform slurry in the dispersion process was less than 30 minutes, B if it was 30 minutes or more but less than 1 hour, and C if it took 1 hour or more.
[0097] [Measurement of viscosity and average particle size d50] The viscosity of the carbon nanotube slurry prepared as described above was measured at a shear rate of 38.3 s using an E-type rotational viscometer (manufactured by Toki Sangyo Co., Ltd., TV-22 model, 1°34′ cone). -1 The measurements were performed at a sample temperature of 25°C. In addition, the average particle diameter d50 of the carbon nanotubes contained in the carbon nanotube slurry prepared as described above was determined from the particle size distribution measured on a volume basis by the laser diffraction method using a laser diffraction / scattering type particle size distribution measurement device (LA-960, manufactured by Horiba, Ltd.).
[0098] <Preparation of Slurry for Electrode Formation> The carbon nanotube slurry prepared as above was mixed with sodium carboxymethylcellulose, SBR (styrene butadiene rubber) emulsion (BM-400B, manufactured by Zeon Corporation) as a binder, and LTO (LTO-2S, manufactured by Beiteru New Energy Materials Co., Ltd.) as an active material for the negative electrode, in a ratio of 1.5 parts by mass of CMC, 1.2 parts by mass of SBR solids, and 97.0 parts by mass of the active material for the negative electrode, relative to 0.3 parts by mass of carbon nanotubes contained in the slurry. Next, the mixture was kneaded using a mixer (THINKY CORPORATION, Awatori Rentaro ARE-310) until a uniform slurry was obtained, to obtain a slurry for forming an electrode (negative electrode).
[0099] <Preparation of electrodes> The prepared electrode-forming slurry was applied to a soda glass piece with a thickness of 50 μm using an applicator. The glass piece on which the electrode-forming slurry was applied was then dried on a hot plate at 90° C. for 10 minutes to prepare an electrode (negative electrode) on which an electrode film was formed. The electrode film formed as the negative electrode contained 0.3 parts by mass of carbon nanotubes, 1.5 parts by mass of CMC, and 1.2 parts by mass of SBR relative to 100 parts by mass of the active material.
[0100] [Measurement of Electrical Resistivity] The surface resistivity (Ω / □) of the obtained negative electrode was measured using an electrical resistivity meter (Mitsubishi Chemical Analytech Co., Ltd., Loresta GP, MCP-T610, four-point probe, ASP pin spacing 5 mm) to evaluate the low electrical resistivity.
[0101] (Examples 2 to 7, Comparative Examples 1 to 6) A carbon nanotube slurry was prepared in the same manner as in Example 1, except that the commercially available carbon nanotubes B to H, the dispersant, the binder, the active material, and the solvent were changed to the types and amounts shown in Table 1. The viscosity of the carbon nanotube slurry and the average particle diameter d50 of the carbon nanotubes contained therein were measured in the same manner as in Example 1.
[0102] Furthermore, each of the prepared electrode-forming slurries was used to prepare electrodes (negative electrodes) in the same manner as in Example 1. The surface resistivity (Ω / □) of each of the obtained electrodes was measured in the same manner as in Example 1.
[0103] Table 1 shows the properties of the carbon nanotubes A to H used in each of the examples and comparative examples. Table 2 shows the types and amounts of carbon nanotubes, dispersants and solvents constituting the carbon nanotube slurries of Examples 1 to 7 and Comparative Examples 1 to 5, as well as the evaluation results of the surface resistivity of electrodes prepared using the same.
[0104] [Table 1]
[0105] [Table 2]
[0106] The carbon nanotube slurries of Examples 1 to 7, which are within the scope of the present invention, had relatively low viscosity and were easily prepared. In contrast, the carbon nanotube slurry of Comparative Example 4, which is outside the scope of the present invention, had low dispersibility and required a long time to prepare.
[0107] Furthermore, the electrode-forming slurries of Examples 1 to 7 within the scope of the present invention were easy to apply to a current collector when producing an electrode. As is clear from Table 2, the electrodes of Examples 1 to 7 produced from the electrode slurries of Examples 1 to 7 within the scope of the present invention exhibited low surface resistivities.
[0108] In contrast, the electrodes prepared from the electrode slurries of Comparative Examples 1 to 5, which are outside the scope of the present invention, exhibited high surface resistivity, as is clear from Table 2. In particular, the electrodes of Comparative Examples 1 and 5 had surface resistivities exceeding 10,000,000 Ω / □, and were clearly inferior in performance as electrodes for lithium secondary batteries. The electrodes of each Comparative Example used carbon nanotubes that are outside the scope of the present invention, and it is believed that good conductive paths were not formed in the prepared electrodes. [Industrial Applicability]
[0109] The carbon nanotube slurry or the electrode forming slurry of the present invention can be used to prepare good electrodes for lithium secondary batteries.
Claims
1. At least carbon nanotubes, a dispersant and a solvent are included, The carbon nanotube is 30 m 2 / g to 70m 2 / g and a peak intensity ratio G / D in Raman spectroscopy of 1.9 or more and 2.3 or less. However, the peak intensity ratio G / D is 1570 cm -1 ~1620cm -1 The maximum intensity of the G band scattered light peak in the range of 1320 cm -1 ~1370cm -1 The maximum intensity of the D band scattered light peak in the range is defined as D, and the ratio is expressed as D.
2. 2. The carbon nanotube slurry according to claim 1, wherein the carbon nanotubes have a fiber length of 500 μm to 3500 μm, a fiber width of 20 nm to 100 nm, and a 2θ peak half width of 0.7° to 1.2° in powder X-ray diffraction analysis.
3. 2. The carbon nanotube slurry according to claim 1, wherein the carbon nanotube content is 0.1% by mass to 3.0% by mass based on the total amount of the slurry.
4. At least carbon nanotubes, a dispersant, an active material, and a solvent are included, The carbon nanotube is 30 m 2 / g to 70m 2 / g and a peak intensity ratio G / D in Raman spectroscopy of 1.9 or more and 2.3 or less. However, the peak intensity ratio G / D is 1570 cm -1 ~1620cm -1 The maximum intensity of the G band scattered light peak in the range of 1320 cm -1 ~1370cm -1 The maximum intensity of the D band scattered light peak in the range is defined as D, and the ratio is expressed as D.
5. 5. The electrode-forming slurry according to claim 4, wherein the carbon nanotubes have a fiber length of 500 μm to 3500 μm, a fiber width of 20 nm to 100 nm, and a 2θ peak half width of 0.7° to 1.2° in powder X-ray diffraction analysis.
6. An electrode film produced by using the electrode forming slurry according to any one of claims 4 to 5.
7. An electrode film containing at least 0.05 to 3.0 mass % of carbon nanotubes, 0.0125 to 6.0 mass % of a dispersant, and 80 to 98 mass % of an active material relative to the total amount of the electrode film, The carbon nanotube is 30 m 2 / g to 70m 2 / g and a peak intensity ratio G / D in Raman spectroscopy of 1.9 or more and 2.3 or less. However, the peak intensity ratio G / D is 1570 to 1620 cm in the Raman spectrum. -1 The maximum intensity of the G band scattered light peak in the range of 1320 to 1370 cm is G. -1 The maximum intensity of the D band scattered light peak in the range is defined as D, and the ratio is expressed as D.
8. 8. The electrode film according to claim 7, wherein the carbon nanotubes have a fiber length of 500 μm to 3500 μm, a fiber width of 20 nm to 100 nm, and a 2θ peak half width of 0.7° to 1.2° in powder X-ray diffraction analysis.
Citation Information
Patent Citations
Slurry for forming lithium ion battery electrode, manufacturing method of the same, and lithium ion battery
JP2006309958A
Carbon nanotube dispersion liquid and its use
JP2020011873A
Cited By
Carbon material for sodium ion battery negative electrode, preparation method and application
CN120308960A